Study Triple Data Encryption Standart Encryption Algorithm In Windows Communication Foundation Environment - Yesiltepe, Mirsat; Kacmaz, Ece; Kurulay, Muhammet (IEEE, 2016)
Today, the concept has left the place of the concept of the internet to cloud. But security is still a problem in web services continues to be, as in all areas. The speed and security are two essential quality criteria behavior shows almost the opposite of each other. This study aims encryption algorithms used by the security mechanisms in their web service veiling results with encryption algorithms to compare test results generated in other environment. The criteria to be used in the name of the encryption algorithm comparison, the key length, the number of clients is the length of messages to be encrypted, and the type of protocol used for communication. TripleDES encryption algorithm will be used. The main three results obtained in this study these are; HTTP protocol is more secure than TCP, asymmetric encryption algorithms, symmetric encryption algorithms to accelerate and HTTP is that it is faster than the TCP protocol.
Keywords: Computer Science; Engineering